Functional characterization and differential expression studies of squalene synthase from Withania somnifera - Gupta, Neha; Sharma, Poonam; Kumar, R. J. Santosh; Vishwakarma, Rishi K.; Khan, Bashir Mohammad (Molecular Biology Reports, 2012)
Squalene synthase (SQS: EC 2.5.1.21) is a potential branch point regulatory enzyme and represents the first committed step to diverge the carbon flux from the main isoprenoid pathway towards sterol biosynthesis. In the present study, cloning and characterization of Withania somnifera squalene synthase (WsSQS) cDNA was investigated subsequently followed by its heterologous expression and preliminary enzyme activity. Two different types of WsSQS cDNA clones (WsSQS1and WsSQS2) were identified that contained an open reading frames of 1,236 and 1,242 bp encoding polypeptides of 412 and 414 amino acids respectively. Both WsSQS isoforms share 99 % similarity and identity with each other. WsSQS deduced amino acids sequences, when compared with SQS of other plant species, showed maximum similarity and identity with Capsicum annuum followed by Solanum tuberosum and Nicotiana tabacum. To obtain soluble recombinant enzymes, 24 hydrophobic amino acids were deleted from the carboxy terminus and expressed as 6X His-Tag fusion protein in Escherichia coli. Approximately 43 kDa recombinant protein was purified using Ni-NTA affinity chromatography and checked on SDS-PAGE. Preliminary activity of the purified enzymes was determined and the products were analyzed by gas chromatograph-mass spectrometer (GC-MS). Quantitative real-time PCR (qRT-PCR) analysis showed that WsSQS expresses more in young leaves than mature leaves, stem and root.
Keywords: Gas chromatograph-Mass Spectrometer (GC-MS); qRT-PCR; Squalene synthase; Withania somnifera

Functional characterization, homology modeling and docking studies of beta-glucosidase responsible for bioactivation of cyanogenic hydroxynitrile glucosides from Leucaena leucocephala (subabul) - Shaik, Noor M.; Misra, Anurag; Singh, Somesh; Fatangare, Amol B.; Ramakumar, Suryanarayanarao; Rawal, Shuban K.; Khan, Bashir Mohammad (Molecular Biology Reports, 2013)
Glycosyl hydrolase family 1 beta-glucosidases are important enzymes that serve many diverse functions in plants including defense, whereby hydrolyzing the defensive compounds such as hydroxynitrile glucosides. A hydroxynitrile glucoside cleaving beta-glucosidase gene (Llbglu1) was isolated from Leucaena leucocephala, cloned into pET-28a (+) and expressed in E. coli BL21 (DE3) cells. The recombinant enzyme was purified by Ni-NTA affinity chromatography. The optimal temperature and pH for this beta-glucosidase were found to be 45 A degrees C and 4.8, respectively. The purified Llbglu1 enzyme hydrolyzed the synthetic glycosides, pNPGlucoside (pNPGlc) and pNPGalactoside (pNPGal). Also, the enzyme hydrolyzed amygdalin, a hydroxynitrile glycoside and a few of the tested flavonoid and isoflavonoid glucosides. The kinetic parameters K (m) and V (max) were found to be 38.59 mu M and 0.8237 mu M/mg/min for pNPGlc, whereas for pNPGal the values were observed as 1845 mu M and 0.1037 mu M/mg/min. In the present study, a three dimensional (3D) model of the Llbglu1 was built by MODELLER software to find out the substrate binding sites and the quality of the model was examined using the program PROCHEK. Docking studies indicated that conserved active site residues are Glu 199, Glu 413, His 153, Asn 198, Val 270, Asn 340, and Trp 462. Docking of rhodiocyanoside A with the modeled Llbglu1 resulted in a binding with free energy change (Delta G) of -5.52 kcal/mol on which basis rhodiocyanoside A could be considered as a potential substrate.
Keywords: Glycosyl hydrolase family 1; homology modeling; Leucaena leucocephala; Molecular docking

Functional characterization of a flavonoid glycosyltransferase gene from withania somnifera (Ashwagandha) - Singh, Somesh; Vishwakarma, Rishi. K.; Kumar, R. J. Santosh; Sonawane, Prashant D.; Ruby; Khan, Bashir Mohammad (Applied Biochemistry and Biotechnology, 2013)
Glycosylation of flavonoids is mediated by family 1 uridine diphosphate (UDP)-dependent glycosyltransferases (UGTs). Until date, there are few reports on functionally characterized flavonoid glycosyltransferases from Withania somnifera. In this study, we cloned the glycosyltransferase gene from W. somnifera (UGT73A16) showing 85-92 % homology with UGTs from other plants. UGT73A16 was expressed as a His(6)-tagged fusion protein in Escherichia coli. Several compounds, including flavonoids, were screened as potential substrates for UGT73A16. HPLC analysis and hypsochromic shift indicated that UGT73A16 transfers a glucose molecule to several different flavonoids. Based on kinetic parameters, UGT73A16 shows more catalytic efficiency towards naringenin. Here, we explored UGT73A16 of W. somnifera as whole cell catalyst in E. coli. We used flavonoids (genistein, apigenin, kaempferol, naringenin, biochanin A, and daidzein) as substrates for this study. More than 95 % of the glucoside products were released into the medium, facilitating their isolation. Glycosylation of substrates occurred on the 7- and 3-hydroxyl group of the aglycone. UGT73A16 also displayed regiospecific glucosyl transfer activity towards 3-hydroxy flavone compound, which is the backbone of all flavonols and also for a chemically synthesized compound, not found naturally. The present study generates essential knowledge and molecular as well as biochemical tools that allow the verification of UGT73A16 in glycosylation.
Keywords: Flavonoid; glycosylation; Glycosyltransferase; Hypsochromic shift; Plant secondary product glycosyltransferase (PSPG); Withania somnifera

Functional characterization of a glucosyltransferase specific to flavonoid 7-O-glucosides from withania somnifera - Kumar, R. J. Santosh; Ruby; Singh, Somesh; Sonawane, Prashant D.; Vishwakarma, R. K.; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2013)
Flavonoids are a large class of phenylpropanoid-derived secondary metabolites, which are usually glycosylated by UDP-glycosyltransferases with one or more sugar groups. Here, we report the cloning and biochemical characterization of a flavonoid glycosyltransferase gene from Withania somnifera (WsGT), which is an important medicinal plant used in Ayurvedic formulations. Using PCR primers, designed for a highly conserved region of previously reported glycosyltransferases, we were able to isolate the corresponding fragment of the WsGT gene. Rapid amplification of cDNA ends (RACE) was then employed to isolate full-length cDNA, which had an open reading frame of 1,371 bp that encode for 456 amino acids. Phylogenetic analysis indicated that WsGT was similar to that of family 1 GT-B glycosyltransferase. Biochemical analysis revealed that WsGT interacts with UDP-glucose and was capable of regiospecifically glycosylating flavonoid-7-ols, such as apigenin, naringenin, luteolin, diadzein and genistein. Expression profiling studies showed that WsGT was highly expressed in young and mature leaves of W. somnifera. Furthermore, exposure to salicylic acid enhanced the expression of WsGT in the leaves and heat shock treatment resulted in decreased expression of WsGT after an initial increase. This may suggest the role of WsGT in response to abiotic/biotic stresses.
Keywords: Diadzein; Flavonoids; Glycosyltransferase; Withania somnifera

Functional and conformational transitions of mevalonate diphosphate decarboxylase from Bacopa monniera - Shakeel, Abbassi; Patel, Krunal; Khan, Bashir Mohammad; Bhosale, Siddharth H.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2016)
Functional and conformational transitions of mevalonate diphosphate decarboxylase (MDD), a key enzyme of mevalonate pathway in isoprenoid biosynthesis, from Bacopa monniera (BmMDD), cloned and overexpressed in Escherichia coli were studied under thermal, chemical and pH-mediated denaturation conditions using fluorescence and Circular dichroism spectroscopy. Native BmMDD is a helix dominant structure with 45% helix and 11% sheets and possesses seven tryptophan residues with two residues exposed on surface, three residues partially exposed and two situated in the interior of the protein. Thermal denaturation of BmMDD causes rapid structural transitions at and above 40 degrees C and transient exposure of hydrophobic residues at 50 degrees C, leading to aggregation of the protein. An acid induced molten globule like structure was observed at pH 4, exhibiting altered but compact secondary structure, distorted tertiary structure and exposed hydrophobic residues. The molten globule displayed different response at higher temperature and similar response to chemical denaturation as compared to the native protein. The surface tryptophans have predominantly positively charged amino acids around them, as indicated by higher K-SV for IC as compared to that for CsCl. The native enzyme displayed two different lifetimes, vi (1.203 +/- 0.036 ns) and tau 2 (3.473 +/- 0.12 ns) indicating two populations of tryptophan. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Aggregation; CD spectroscopy; Fluorescence quenching; Mevalonate diphosphate decarboxylase; Unfolding